Marketing and Branding of Teacher Education in Khyber Pakhtunkhwa, Pakistan: Teacher Education Providers’ Struggles for Prospective Entrants - Gulab Khan, Asif Khan, Munazza Sultana (PJE, 2023)
Pakistan’s National Educational Policy 2009 delineates that quality of teacher certifications in primary and secondary tiers of education willprogressively be made more rigorous by replacing the erstwhile Primary Teaching Certificate (PTC) and Certificate of Teaching (CT) programs. For this and similar policy provisions, in the last two decades, Pakistan has witnessed a rapid increase in the number of private and public Teacher Education Providers (TEPs) that provide alternate and supposedly more rigorous certifications such as the Bachelor of Education. As a result, struggles have ensued among the TEPs to bag their market share of thepotential applicants to their teacher education programs. T